2019
DOI: 10.5194/se-2019-18
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seismic attenuation and dispersion in poroelastic media with fractures of variable aperture distributions

Abstract: Abstract. Considering poroelastic media containing aligned periodic fractures, we numerically quantify the effects that fractures with variable aperture distributions have on seismic wave attenuation and velocity dispersion due to fluid pressure diffusion (FPD). To achieve this, realistic models of fractures are generated with a stratified percolation algorithm which provides statistical control over geometrical fracture properties such as density and distribution of contact areas. The results are sensitive to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This may have some influence on the frequency‐dependent P wave anisotropy. However, a recent study of Lissa et al (2019) showed that the seismic response of fractures with realistic thickness (aperture) distributions (including multiple contacts) can be emulated by fractures of constant thickness with equivalent poroelastic infills accounting for effects of thickness variations. Such fractures with poroelastic infills can be approximated by void fractures with equivalent fracture compliances (Guo, Rubino, et al, 2018a, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…This may have some influence on the frequency‐dependent P wave anisotropy. However, a recent study of Lissa et al (2019) showed that the seismic response of fractures with realistic thickness (aperture) distributions (including multiple contacts) can be emulated by fractures of constant thickness with equivalent poroelastic infills accounting for effects of thickness variations. Such fractures with poroelastic infills can be approximated by void fractures with equivalent fracture compliances (Guo, Rubino, et al, 2018a, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…The seismic response of a fractured Berea sandstone is numerically modeled considering a poroelastic upscaling approach (Lissa et al., 2019; Masson & Pride, 2007; Quintal et al., 2011). For that, we solve the quasi‐static Biot's equations (Biot, 1941) in the frequency domain, which are bold-italicσ=0, iωboldw=)(κηp, where bold-italicσ is the total stress tensor, w is the relative fluid displacement vector, p is the fluid pressure, ω is the angular frequency and i is the complex unity.…”
Section: Methodsmentioning
confidence: 99%
“…That is, a medium containing a periodic repetition in the vertical z ‐direction of semihorizontal fractures having infinite length in the x ‐direction and y ‐direction. In addition, the applied boundary conditions account for the strain and stress field interactions of consecutive fractures (Lissa et al., 2019; Milani et al., 2016). The mathematical description of the applied boundary conditions is given in Appendix A.…”
Section: Methodsmentioning
confidence: 99%
“…In order to study the role played by the roughness of the cracks on the squirt flow mechanism, the aperture distribution of the cracks has been generated following the approach introduced by Nolte and Pyrak‐Nolte (). The full workflow for the model generation is described by Lissa et al ().…”
Section: Methodsmentioning
confidence: 99%